Total and Structural Carotid Artery Stiffness Are Associated With Cognitive Decline and Structural Brain Abnormalities Related to Alzheimer Disease and Alzheimer Disease‐Related Dementias Pathology: The Multi‐Ethnic Study of Atherosclerosis - Jeremy R. Williams; Theodore M. DeConne; Ryan Pewowaruk; Claudia Korcarz; Jordan Tanley; Cynthia Carlsson; Susan R. Heckbert; Mohamad Habes; Ilya Nasrallah; Samuel N. Lockhart; José A. Luchsinger; Jingzhong Ding; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Arterial stiffness is associated with pathological changes underlying Alzheimer disease and related dementias. Total pulse wave velocity can be subdivided into 2 main mechanisms: structural arterial stiffness (S‐PWV) due to intrinsic remodeling of the artery wall and load‐dependent arterial stiffness due to increased blood pressure. Methods and Results In this prospective cohort study, MESA (Multi‐Ethnic Study of Atherosclerosis) participants completed B‐mode carotid ultrasounds from which carotid total pulse wave velocity was calculated. S‐PWV was calculated by adjusting pulse wave velocity to 120/80 mmHg using a nonlinear pressure‐diameter relationship, and load‐dependent arterial stiffness was derived by subtracting S‐PWV from total pulse wave velocity. Participants had repeated cognitive assessments with the Cognitive Abilities Screening Instrument, Digit Symbol Coding, and Digit Span combined into a global cognitive composite (N=2489). Brain magnetic resonance imaging was used to generate total gray matter volume (N=906), white matter hyperintensity volume (N=896), and total white matter fractional anisotropy (N=810). Multivariable linear fixed and mixed effects regression models related standardized pulse wave velocity components to neuroimaging and cognitive decline parameters, respectively. Greater S‐PWV was associated with greater longitudinal cognitive decline in global cognitive composite score (β=–0.05, P=0.002) and subtests, whereas greater load‐dependent arterial stiffness was not associated with longitudinal cognitive decline. Greater S‐PWV was associated with lower gray matter volume (β=–3183.4, P=0.013) and higher log white matter hyperintensity volume (β=0.20, P<0.001), whereas load‐dependent arterial stiffness was associated with lower total white matter fractional anisotropy (β=–0.004, P≤0.001). Conclusions Higher structural stiffness of the carotid artery is associated with cognitive decline, whereas both structural and load‐dependent stiffness are associated with brain structural abnormalities common in Alzheimer disease‐related dementias.